Model Pengelolaan Keuangan Berbasis Literasi Keuangan dan Inklusi Keuangan : Studi pada UMKM di Kota Binjai - Dahrani Dahrani; Fitriani Saragih; Pandapotan Ritonga (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to produce a Model of Financial Management Based on Financial Literacy and Financial Inclusion: A Study on MSMEs in Binjai City. Meanwhile, the research time until the completion stage is estimated to be approximately 8 months from March 2021 to October 2021. This research is basic research. The population and sample in this study were taken from 205 Micro, Small and Medium Enterprises in Binjai City, through collaboration using a cluster sampling approach in 5 sub-districts in Binjai City, as well as random sampling based on the criteria of type, duration, and average level. business profit. Primary data collection was carried out using a survey method using a questionnaire (questionnaire). The data analysis technique used is descriptive statistical analysis and SEM-PLS with the help of Smart PLS software. The results showed that based on the results of data processing from the structural model, the results obtained that the Financial Literacy variable had a significant positive effect on Financial Inclusion: A study on MSMEs in Binjai City. Financial Literacy has a significant positive effect on Financial Management: Study on MSMEs in Binjai City. Financial Inclusion has a significant positive effect on Financial Management, and Financial Inclusion can positively mediate Financial Literacy on Financial Management: Study on MSMEs in Binjai City.